Percepção de risco e vulnerabilidade social dos moradores de Ajuruteua. - OLIVEIRA, Ubiranilson Santos de (Universidade Federal do Pará, 2019)
This study investigates the perception of risk and social vulnerability of the residents of Ajuruteua, a beach located 36 km from the town of Bragança-Pará. Part of this area is considered as a very high risk to marine coastal erosion, as noted by the destruction of properties located by the sea. Erosion is a natural event that affects people’s safety and it is triggered by anthropic factors, especially by disorderly occupation. Due to this the government proposes the evacuation of people from risk areas, because they are vulnerable to erosive action. However, it comes across the economic factor of the families involved, since the income of the people living there depends on the fishing, commerce, houses rental, hostels and other activities developed in the coast. In this perspective, this research aimed to verify residents’ perception on the risk of erosion, as well as to record their adaptation to natural events, and to monitor the impacts of removing the vulnerable population from risk areas to the municipality's headquarters. Such a context brings out the following issues: Can the understanding of the risk perception and social vulnerabilities of people living in Ajuruteua contribute to public policies for disaster risk reduction? The methodology was based on theory and method literature review, documentary research in public and private institutions and the application of a script of interviews with local residents and entrepreneurs. The objective of the interviews was to understand and identify the degree of social vulnerability of the resident population in Ajuruteua from the population 's perception of natural erosion events. It is hoped that the study will be able to contribute to public policies for disaster reduction, collaborating with the discussion about the different perceptions about the appropriate use of natural resources available in Ajuruteua.